Treatment of Hereditary Protein C Deficiency with Stanozolol - Broekmans, A W; Conard, J; van Weyenberg, R G; Horellou, M H; Kluft, C; Bertina, R M (Thrombosis and Haemostasis, 1987)
Five type I protein C deficient male patients received 5 mg stanozolol b.i.d. during 4 weeks. After four weeks of treatment plasma protein C activity increased from 0.42 to 0.74 U/ml and protein C antigen from 0.49 to 0.75 U/ml. This approximately 1.6 fold increase in plasma protein C was accompanied by an increase in factor II antigen (1.5 fold), factor V activity (1.6 fold), factor X antigen (1.1 fold), antithrombin III antigen (1.3 fold) and heparin cofactor II antigen (1.5 fold), while the concentration of factor VII, factor VIII, and factor IX activity, and of protein S antigen remained unchanged. Prothrombin fragment F1+2, measured in two patients, increased 1.3 fold. In addition to its effect on procoagulant and anticoagulant factors stanozolol had profibrinolytic effects, reflected in an increase in tPA activity and in the concentration of plasminogen. These data indicate that in type I protein C deficient patients stanozolol increases the concentrations of both procoagulant and anticoagulant factors and favours fibrinolysis. The efficacy of stanozolol in preventing thrombotic disease in type I protein C deficient patients, however, remains to be established. During the four weeks of stanozolol treatment no thrombotic manifestations were observed in the protein C deficient patients.
Keywords: Protein C deficiency; Thrombosis; Stanozolol